Subcutaneous Fat Obesity in a High Body Mass Index Donor Is Not a Contraindication to Living Donor Hepatectomy - Hirak Pahari; Amey Sonavane; Amruth Raj; Anup Kumar Agrawal; Ambreen Sawant; Deepak Kumar Gupta; Amit Gharat; Vikram Raut (Case Reports in Hepatology)
Background. Living donor liver transplantation (LDLT) has revolutionized the field of transplantation without compromising donor safety. Donor safety is of paramount concern to the transplant team. BMI >35 kg/m2 is mostly considered a contraindication to liver donation. Here, we present a successful right donor hepatectomy from a donor with a BMI of 36.5 kg/m2. Case Summary. A 39-year-old wife donated her right lobe of liver to her 43-year-old husband with nonalcoholic steatohepatitis-related chronic liver disease (CLD). His indications were refractory ascites, hepatic encephalopathy, acute kidney injury, recurrent elbow and urine infections leading to cachexia. She was initially rejected due to a high BMI but failed to lose weight over the next 2 months, and the need for a transplant in her husband was imminent. With no other potential living donors, we decided to proceed with donor evaluation as she had no other comorbidity. We were surprised to find normal liver function tests and a good liver attenuation index (LAI) of +16 on a computed tomography (CT) scan. Magnetic resonance (MR) imaging revealed a fat fraction of 3%. Volumetry confirmed a remnant of 37.9% and a potential graft-to-recipient weight ratio of 1.23. V/S ratio on CT scan (visceral fat area/subcutaneous fat area at L4-level) was <0.4 confirming subcutaneous fat obesity. Both surgeries were uneventful and both donor and recipient recovered well except recipient re-exploration on postoperative day (POD)-1 due to surgical bleeding. The donor was discharged on POD-6 and recipient was discharged on POD-15. At 3 weeks of follow-up, the donor’s wound is clean and well-healed, and she is already back to doing her daily life activities without any pain with normal laboratory parameters. Conclusion. Subcutaneous fat obesity should not be considered as a contraindication to liver donation even with a BMI >35 kg/m2. A small percentage of healthy individuals will not have visceral fat obesity and may not have steatotic livers. The CT scan and MR fat fraction estimation can confirm the findings. Biopsy may be avoided if MR fat estimation is <10% in obese donors. Intraoperative visualization in these donors remains the gold standard to decide the need for biopsy. Living donor hepatectomy may be safely performed in a select group of high BMI patients (>35 kg/m2) with pure subcutaneous fat obesity in the absence of other suitable living donors.